Sport - In Praise of Doping on its Usefulness and Necessity - Kosiewicz Jerzy (Sciendo, 2017)
The author points out that in contemporary competitive, record oriented, professional, spectacular, top-level sport, elite sport, marketability sport or Olympic sport - whose beginnings should be dated to the turn of the 19th and the 20th century - mistaken decisions, which inhibited development of the abovementioned forms of sport, took place.